METFORMIN IS LINKED TO REDUCED MORTALITY IN TYPE 2 DIABETES WITH COMORBID CKD AND CHF: A SYSTEMATIC REVIEW - Andreria Hatulely, Chrysman (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2023)
Introduction: Due to DM diagnosis criteria, determining its incidence is difficult. Diabetes affects 10.2 million Americans. Due to conflicting data on mortality and antihyperglycemic therapy benefits, managing hyperglycemia in type 2 diabetes mellitus (T2DM) patients at risk of cardiovascular problems is difficult.The aim: This article showed about metformin is Linked to reduced mortality in type 2 diabetes with comorbid chronic kidney disease (CKD) and congestive heart failure (CHF).Methods: By comparing itself to the standards set by the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) 2020, this study was able to show that it met all of the requirements. So, the experts were able to make sure that the study was as up-to-date as it was possible to be. For this search approach, publications that came out between 2013 and 2023 were taken into account. Several different online reference sources, like Pubmed and SagePub, were used to do this. It was decided not to take into account review pieces, works that had already been published, or works that were only half done.Result: In the PubMed database, the results of our search brought up 85 articles, whereas the results of our search on SagePub brought up 57 articles. The results of the search conducted for the last year of 2013 yielded a total 34 articles for PubMed and 21 articles for SagePub. In the end, we compiled a total of 19 papers, 13 of which came from PubMed and seven of which came from SagePub. We included five research that met the criteria.Conclusion: Metformin use was found to be related with a reduced risk of death from any cause as well as progression toward ESRD in patients with CKD and CHF in the current investigation.